On MLMDA/Butterfly Compressibility of Inverse Integral Operators - Guo, Han; Hu, Jun; Michielssen, Eric (IEEE antennas and wireless propagation letters, 2013)
The multilevel matrix decomposition algorithm (MLMDA) is shown to permit effective compression of inverse integral operators pertinent to the analysis of scattering from electrically large structures. Observed compression ratios exceed those realized by low-rank (LR) compression methods, leading to substantial memory savings and a faster application of the inverse operator, and suggesting a new application for schemes traditionally used for compressing forward integral operators.